Enhancing Brand Loyalty Through Consumer-Celebrity Congruence in the Hospitality Sector - Nguyễn, Văn Anh (Middlesex University Mauritius, 2024)
This study aims to investigate how consumer-celebrity match impacts brand engagement and loyalty in the hospitality industry with an effort to understand better consumer-celebrity marketing and its underlying principles the Meaning Transfer Model (MTM) and Customer Brand Engagement (CBE) were applied to assess the direct and indirect impacts of measurement model variables on celebrity marketing. The quantitative methodology was used in this study with data from 490 respondents. The outcome reveals that consumer-celebrity match has a favourable effect on brand engagement and brand engagement also leads to a positive correlation with brand loyalty. The research provides insightful conclusions for managers looking to optimize their marketing strategy based on the result.